Praktik Jual Beli Ikan Potong - Tusaddia, Halimah; Hasibuan, Zulfan Efendi (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
In human life buying and selling is a necessity that cannot be abandoned, so humans cannot live without buying and selling activities. Buying and selling is also a means of helping fellow human beings so that Islam determines its permissibility. In line with the times, the problem of buying and selling occurs in society is increasingly widespread. One of them is the practice of buying and selling cut fish at the Inpres Market in Sibolga City. The problem in this study is how to buy and sell cut fish at the Inpres Market in Sibolga City and how the relationship between fiqh muamalah and the practice of buying and selling cut fish at the Inpres Market in Sibolga City.The basic theory used in this study is the understanding of buying and selling, the legal basis of buying and selling, the pillars of buying and selling, the legal terms of buying and selling, khiyar in buying and selling, various kinds of buying and selling, rights and obligations of buying and selling, and the wisdom of buying and selling.This research is a field research. Research conducted by collecting data on phenomena that occur, natural and natural. The data sources of this research are primary data and secondary data. Data collection techniques used field studies, namely observation, interviews, and documentation.The results showed that the practice of buying cut fish at the Inpres Market in Sibolga City contained an element of ambiguity regarding the sale and purchase contract, namely the buying and selling of fish carried out at the Inpres market was divided into two ways, namely buying and selling fish which was done by cutting and buying and selling fish which was done indirectly cut. People who buy fish uncut will get whole fish while people who buy fish in pieces, the seller will reduce the benefits of the fish without an agreement that the seller will take eggs from the fish that will be cut by the seller so that they get more profit from taking the fish eggs . Based on muamalah fiqh, it is not permissible to buy and sell that is deceptive or gharar and there is an ambiguity in the contract of buying and selling fish. Therefore, the sale and purchase of cut fish at the Inpres Market in Sibolga City is not permitted.